2015
DOI: 10.14348/molcells.2015.0078
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Clinical Implications of Novel MYO15A Mutations in a Non-consanguineous Korean Family by Targeted Exome Sequencing

Abstract: Mutations of MYO15A are generally known to cause severe to profound hearing loss throughout all frequencies. Here, we found two novel MYO15A mutations, c.3871C>T (p.L1291F) and c.5835T>G (p.Y1945X) in an affected individual carrying congenital profound sensorineural hearing loss (SNHL) through targeted resequencing of 134 known deafness genes. The variant, p.L1291F and p.Y1945X, resided in the myosin motor and IQ2 domains, respectively. The p.L1291F variant was predicted to affect the structure of the actin-bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 44 publications
(82 reference statements)
2
19
0
Order By: Relevance
“…The IHC protocol for PTEN , MET (MET proto‐oncogene, receptor tyrosine kinase), and HER2 for the trial were previously reported . Somatic alterations were detected by targeted deep sequencing by CancerSCAN, as previously reported . From August 2014 through January 2015, we applied CancerSCAN version 1 consisting of 83 cancer‐related genes ( n = 167), and from February 2015, CancerSCAN version 2 was applied, encompassing 381 cancer‐related genes ( n = 251).…”
Section: Methodsmentioning
confidence: 99%
“…The IHC protocol for PTEN , MET (MET proto‐oncogene, receptor tyrosine kinase), and HER2 for the trial were previously reported . Somatic alterations were detected by targeted deep sequencing by CancerSCAN, as previously reported . From August 2014 through January 2015, we applied CancerSCAN version 1 consisting of 83 cancer‐related genes ( n = 167), and from February 2015, CancerSCAN version 2 was applied, encompassing 381 cancer‐related genes ( n = 251).…”
Section: Methodsmentioning
confidence: 99%
“…The obtained reads were aligned to the UCSC hg19 reference genome (http://genome.ucsc.edu/index.html) and variants were filtered. Further bioinformatics analyses were performed as previously described [23]. If the results of these steps were not convincing, WES was performed.…”
Section: Methodsmentioning
confidence: 99%
“…[Ammar‐Khodja et al., ], [Atik et al., ], [Bademci et al., ],[Bashir et al., ], [Belguith et al., ], [Brownstein et al., ], [Brownstein et al., ], [Cengiz et al., ], [Chang et al., ], [Chen et al., ], [Diaz‐Horta et al., ], [Duman et al., ], [Fattahi et al., ], [Gao et al., ], [Gu et al., ], [Imtiaz et al., ], [Kalay et al., ], [Lezirovitz et al., ], [Li et al., ], [Liburd et al., ], [Miyagawa et al., ; Miyagawa et al., ], [Miyagawa et al., ], [Moteki et al., ], [Nal et al., ], [Neveling et al., ], [Park et al., ], [Rehman et al., ], [Riahi et al., ], [Schrauwen et al., ], [Shafique et al., ], [Shahin et al., ], [Shearer et al., ], [Sloan‐Heggen et al., ], [Sloan‐Heggen et al., ], [Vona et al., ], [Vozzi et al., ], [Wang et al., ], [Woo et al., ], [Xia et al., ], [Yano et al., ], [Yang et al., ]…”
Section: Articles Cited In the Online Supporting Informationmentioning
confidence: 99%